A triangular-grid finite-difference time-domain method for electromagnetic scattering problems - Lee, C.F.; Mccartin, B.J.; Shin, R.T.; Kong, J.A. (Journal of electromagnetic waves and applications, 1994)
A two-dimensional (2-D) finite-difference time-domain (FDTD) method using a triangular grid is introduced for solving electromagnetic scattering problems. The 2-D FDTD method is based on a control region approximation, which is defined by the Dirichlet tessellation of the triangular grid. In general, this discretization scheme is accurate to second-order in time, to first-order in space for non-uniform grids, and to second-order in space for uniform grids. Using triangular grids, arbitrary geometries can be represented by piecewise linear models . In addition, an absorbing boundary condition on a smooth outer boundary, such as a circular boundary, can be implemented. This method is illustrated and verified by calculating scattering from perfectly conducting and coated objects. It is shown that geometrical modeling using a triangular grid is more accurate for electromagnetic scattering problems than those using a rectangular grid, especially when the surface wave is significant.